Race and Genealogy. Buffon and the Formation of the Concept of “Race” - Claude-Olivier Doron (Humana.Mente: Journal of Philosophical Studies, 2012)
This article analyses the conditions of formation of the concept of “race” in natural history in the middle of the eighteenth century. Relying on the method of historical epistemology to avoid some of the aporias raised by the traditional historiography of “racism”, it focuses on the peculiarities of the concept of “race” in contrast to other similar concepts such as “variety”, “species” and tries to answer the following questions: to what extent the concept of “race” was integrated in natural history’s discourses before the middle of the eighteenth century? To which kind of concepts and problems was it linked and to which style of reasoning did it pertain? To which conditions could it enter natural history and develop in it? The article argues that “race” pertained to a genealogical style of reasoning which was largely extraneous to natural history before the middle of the eighteenth century. Natural history was rather dominated by a different style of reasoning, a logical and classificatory style, whose principles and concepts were strong obstacles to the development of a concept of “race”. To understand how the concept of “race” developed in natural history, one should understand how the genealogical style of reasoning entered natural history and modified the very principles of classification that organized it. I try to establish that it is through Buffon and some of the main authors of the “monogenist” tradition that the most fundamental conditions for the integration of a genealogical style of reasoning and the development of a concept of “race” are met. To put it clearly, in contrast to many scholars’ analysis – and following some intuitions of P.R Sloan – I argue that Buffon in particular, and monogenism in general, were decisive in the integration and development of the concept of “race” in natural history.